Promotion of bone regeneration on titanium implants through a chemical treatment process using calcium phosphate slurry: Microscopic analysis, cellular response, and animal experiment. Issue 7 (16th February 2018) - Ito, Tatsuro; Ohtsu, Naofumi; Tomozawa, Masanari; Hirano, Mitsuhiro; Takita, Hiroko; Iizuka, Tadashi; Yokoyama, Atsuro
Abstract: The present study provides scientific evidence that a new chemical treatment process using calcium phosphate slurry promotes bone regeneration on titanium (Ti) implants. The material's surface modified by the treatment was analyzed using microscopic observation and the bone regeneration efficacy was evaluated both in vitro and in vivo . Formation of a thin hydroxyapatite layer with a thickness of about 50 nm and an increase of surface roughness were confirmed by microscopic observations. Histological evaluation of rat femora implanted with the specimens showed that the areas of the specimens directly attached to bone tissue were significantly more extensive than those implanted with control Ti at 2 and 8 weeks. Likewise, on the treated Ti, ALP activity, osteopontin, osteocalcin, and calcium contents of rat bone marrow stromal cells were significantly higher than on the control Ti. Furthermore, reverse transcription polymerase chain reaction showed greater expression of messenger ribonucleic acid encoding Cbfa1 and collagen type1 on the treated Ti at 2 weeks. Based on these results, we concluded that the new process was effective to enhance the osteoconductivity of Ti. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 2716–2724, 2018.